Effect of vegetal-oil emulsion and passion fruit peel-powder on sensory acceptance of functional yogurt. (April 2015) - Perina, N.P.; Granato, D.; Hirota, C.; Cruz, A.G.; Bogsan, C.S.B.; Oliveira, M.N.
Abstract: Vegetal oil emulsion and passion fruit peel powder were concomitantly incorporated to milk aiming to produce new functional yogurt with health benefits. Four milk bases with similar energetic content and macronutrient composition, enriched or not with vegetal oil emulsion and/or passion fruit peel powder, were fermented with Streptococcus thermophilus, Lactobacillus delbrueckii subsp. bulgaricus and Bifidobacterium lactis ( Bifidobacterium species 420) to supply yogurts with similar appearance, flavor, and stability. Milk without supplementation was used as control. Applying hedonic scale and projective map approaches, respectively, 227 and 25 panelists analyzed the samples concerning flavor, texture-in-spoon, creaminess-in-mouth, and global impression. Instrumental firmness was also investigated. Considering the same fermentation temperature, the addition of vegetal-oil emulsion and passion fruit peel-powder did not influence fermentation time, but significantly affected instrumental firmness. Despite the observed differences in flavor and global impression there were no significant changes in consumers' overall liking between supplemented and conventional yogurts. Highlights: Supplementation of milk in yoghurt manufacture can be attractive for consumers. Vegetal-oil emulsion can afford possible health benefits. Passion fruit peel-powder addition can provide potential health benefits. Vegetal oil emulsion incorporation alters yogurt's structure with effect in firmness. Supplementation affects flavor and global impression, but not overall liking.